A budget management system construction - Aimurzinov, M.S.; Baimukhamedova, G.S.; Baimukhamedov, М.F. (BUKETOV BUSINESS REVIEW, 2019)
Тhe construction of a budgeting system is an extremely important stage in the organization and development of a manufacturing enterprise. You should not assume that the introduction of a budgeting system in an enterprise will only require appropriate configuration of an information automated enterprise management system. Of course, much but not everything depends on the information security of the enterprise in this complex process of budgeting. The decisive role in the formulation of the budgeting system and the improvement of the existing budgeting system in an enterprise is played by the professionalism and involvement of financial management. The transition to a full-fledged budgeting system in the company and the budget management system is impossible without a serious structural change throughout the organization, since setting up an effective budgeting system requires that management and employees have serious, verified, coordinated and focused work. Budget is a key management tool. The purpose of this study is to find solutions to improve the efficiency of the budget system within economic entities. The first part of the article highlights the benefits of implementing budgets and budget control in enterprises. The article proposes measures and actions that need to be taken to limit negative aspects and achieve an effective budget system so that the budget is considered as a management tool that integrates into a wider review of performance.